Lithographic fabrication and spectroscopic characterization of a THz metamaterial absorber - Tung, Nguyen Thanh; Phuc, Le Hong (Vietnam Journal of Science and Technology, 2021)
THz metamaterial absorbers are often studied by computational techniques, where the influence of actual material parameters and fabricating limitation has not been completely understood. Here we present an experimental investigation on a far-infrared metamaterial absorber composed of a gold disk-shaped resonator, a silicon oxide spacer, and a gold film. The samples are fabricated using the UV laser lithography technique in combination with the electron-beam evaporation. The absorption feature of fabricated samples is examined by Fourier-transformed infrared spectroscopy and supported by finite integration simulations.